Pengaruh Sistem Akuntansi Kas Kecil Dan Rekonsiliasi Bank Terhadap Efektivitas Pengendalian Kas Pada Koperasi Sejahtera Bersama - Sutarti, Sutarti; Muanas, Muanas; Purnama, Mega (Institut Bisnis dan Informatika Kesatuan, 2015)
Protecting cash and ensuring the accuracy of cash accounting records in the effective control of cash is a must. Good controlling avoid the fraud of change the reports and calculations, the existence of appropriate records procedure so that appropriate controlling to assets, debts, income and expenses can be done. The purposes of this research are to analyse and explore the process of establishing petty cash and bank reconciliation and its effect on a company's intemal control cash. The research is conducted at Koperasi Sejahtera Bersama which is located in Bogor. Koperasi Sejahtera Bersama is a cooperative that serves as a financial institution that raise and distribute funds from and to the public. The result of the research showed that Koperasi Sejahtera Bersama has been using petty cash accounting system and bank reconciliation on cash control effectiveness. The effective control in this company must be maintained in order to achieve the expected goals and objectives. Keywords: accounting, petty cash, reconciliation, control